Mampu Memilih Dan Menentukan Bahan Pembelajaran - Fernidia Br. Siburian; Dorlan Naibaho (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
Basically, learning is a process carried out by teachers and students to create changes in the behavior of individual students. Changes that occur as a result of learning can take place in various forms, such as skills, habits, attitudes, acceptance, or appreciation, which include aspects of self-state, knowledge, or individual actions. In line with professional responsibility as a teacher, it is important for them to always prepare everything related to the learning program in carrying out learning activities. This assessment aims to find out the ability to choose and determine learning materials. This is a challenge for both teachers and learners. The research method applied in this paper is a qualitative method, suitable for investigating conditions or situations in an educational context. The literature study approach is used to collect information from various sources such as books and journals, which aim to support and complement the discussion. This objective must be in line with the competency standards and basic competencies that learners want to achieve. Therefore, the selected learning materials must really support the achievement of the basic competency standards and indicators that have been set. In the selection of learning materials, it is necessary to consider the type, scope, sequence, and way of presenting the material. Success is influenced by factors such as learning structure, student motivation, teacher expectations, classroom questions, and time optimization Finally, the discussion of character education includes the selection of a character education model that suits the school situation and delivery methods that are in line with the model. Methods such as modeling, active student participation, democracy, co-discovery, and hands-on learning are described as ways to deliver character education to students.